2005
DOI: 10.1093/ajcn/82.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Different modes of weight loss in Alzheimer disease: a prospective study of 395 patients

Abstract: During the follow-up of patients with Alzheimer disease, risk factors for these 2 modes of weight loss should be sought to identify patients who would benefit from a nutritional intervention. Our findings lead us to advocate follow-up, which involves an assessment of functional, nutritional, and neuropsychologic status every 6 mo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(45 citation statements)
references
References 23 publications
4
28
0
13
Order By: Relevance
“…23 Weight at baseline was higher for patients who lost weight or regained only <5% of weight than for patients whose weight increased. These findings are in line with Guérin et al 24 whose follow-up study on elderly patients with Alzheimer disease found that higher weight and BMI at baseline correlated with higher subsequent weight loss. Likewise, weight gain in elderly people was associated with a lower baseline weight and BMI compared to those whose weights were stable.…”
Section: Discussionsupporting
confidence: 91%
“…23 Weight at baseline was higher for patients who lost weight or regained only <5% of weight than for patients whose weight increased. These findings are in line with Guérin et al 24 whose follow-up study on elderly patients with Alzheimer disease found that higher weight and BMI at baseline correlated with higher subsequent weight loss. Likewise, weight gain in elderly people was associated with a lower baseline weight and BMI compared to those whose weights were stable.…”
Section: Discussionsupporting
confidence: 91%
“…The growing knowledge of the pathophysiologic factors associated with the development of malnutrition in Alzheimer patients underscores this prevalence data from MNA studies. Progressing dementia, institutionalization, hospitalization, infectious complications, and other examples of acute disease have been identified as risk factors for rapid weight loss and physical decline in this population 42 …”
Section: Results and Relevance Of The Mna In Various Settingsmentioning
confidence: 99%
“…Many studies have shown that there is a trend to lose weight during the illness for patients with Alzheimer's disease (AD) (White et al ., ; Guérin et al ., ). Weight loss may be associated with protein and energy malnutrition leading to severe complications such as alterations of the immune system, muscular atrophy and so on (Gillette Guyonnet et al ., ) and is a risk factor of adverse outcomes during the course of AD such as mortality (White et al ., ; Vellas et al ., ), institutionalization (Andrieu et al ., ; Vellas et al ., ), progression of cognitive impairment (White et al ., ) and loss of functional autonomy (Vellas et al ., ; Spaccavento et al ., ).…”
Section: Introductionmentioning
confidence: 97%